The Historicization of “Religion” and The Devastation of Study of Religion Departments: Siamese Twins or Contingent Acquaintances? - Taira, Teemu (Implicit religion, 2020)
Two main arguments of Timothy Fitzgerald’s The Ideology of Religious Studies (2000) (IRS) are that religion is an analytically useless (and even harmful) category and that study of religion departments could be rearranged as departments of cultural studies, theoretically informed ethnographic studies or humanities that study the institutionalized values of specific societies. This article introduces Fitzgerald’s argument, examines the reception of Fitzgerald’s work, and then proceeds to argue that, contrary to the opinion of many commentators, Fitzgerald’s first criticism opens up important research possibilities for scholars of religion. However, this article takes a slightly more critical view on the second argument, despite agreeing with the necessity of interdisciplinary research. Finally, this article suggests that historicizing the category of religion can enliven study of religion departments, rather than representing a reason for their problems.